Effects of Phytase Supplementation on Performance, Bone Chara Cteristics, Blood Minerals and Calcium and Phosphorus Retention in Broiler Quails - Sheikhlar, Atefeh (2009)
Two experiments were conducted to determine the appropriate ratio of calcium (Ca) and total phosphorus (tP) (to be used for the second experiment) capable to elicit good response on the addition of dietary phytase to broiler quail's diet, and to study the effect of varying levels of this enzyme on the growth performance, Ca and P retention, plasma's Ca and P, crude protein (CP) and phytate P (pP) retention and bone characteristics in broiler quails. In the first experiment 600 quail s were subjected randomly to 5 treatments consisting ratios of Ca and tP: 1.39, 1.53, 1 .66 (normal ratio), 1 .8 1 , and 1 .96. Each treatment was replicated four times, consisting of 30 birds per replicate. The experimental period was 21 days. The second experiment used 480 quails, birds were randomly distributed into five treatment groups consisting of different levels of microbial phytase supplementation of 0, 250, 500, 750, 1000 FrU (phytase u nits). Each treatment was replicated four times, consisting of 24 birds per replicate, and experi mental period was also 21 days. Basal diet was based on corn and soybean meal.